2016
DOI: 10.1002/pros.23295
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal and Non-Exosomal Urinary miRNAs in Prostate Cancer Detection and Prognosis

Abstract: Plasma exosomal miRNAs were evaluated for prognosis in an initial set of 44 metastatic renal cell cancer (mRCC) patients by RNA sequencing. Among ~3.49 million mappable reads per patient, miRNAs accounted for 93.1% of the mapped RNAs. 227 miRNAs with high abundance were selected for survival analysis. Cox regression analysis identified association of 6 miRNAs with overall survival (OS) (P<0.01, False discovery rate (FDR) < 0.3). Five of the associated miRNAs were quantified in an independent follow-up cohort o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
129
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(135 citation statements)
references
References 50 publications
4
129
1
1
Order By: Relevance
“…In an independent cohort of 28 prostate cancer patients and 19 healthy men, miR‐196a‐5p and miR‐501‐3p were significantly decreased in the urine from the prostate cancer patients by qPCR, and the AUCs of miR‐196a‐5p and miR‐501‐3p were 0.73 and 0.69, respectively, for the detection of cancer . Other groups reported that miR‐21 and miR‐375 in urinary exosomes were elevated, but that miR‐19b and miR‐125b were decreased in prostate cancer patients …”
Section: Evs (Exosomes) In Urinementioning
confidence: 98%
See 1 more Smart Citation
“…In an independent cohort of 28 prostate cancer patients and 19 healthy men, miR‐196a‐5p and miR‐501‐3p were significantly decreased in the urine from the prostate cancer patients by qPCR, and the AUCs of miR‐196a‐5p and miR‐501‐3p were 0.73 and 0.69, respectively, for the detection of cancer . Other groups reported that miR‐21 and miR‐375 in urinary exosomes were elevated, but that miR‐19b and miR‐125b were decreased in prostate cancer patients …”
Section: Evs (Exosomes) In Urinementioning
confidence: 98%
“…69 Other groups reported that miR-21 and miR-375 in urinary exosomes were elevated, but that miR-19b and miR-125b were decreased in prostate cancer patients. 70,71 Exosomes can contain the characteristics of the metabolites in prostate cancer cells. The metabolome analysis of urinary exosomes from 62 patients with prostate cancer and 42 healthy individuals showed significant differences in 28 metabolites between the exosomes from patients with prostate cancer and those from healthy individuals, of which 27 metabolites were significantly lower in the exosomes from the men with prostate cancer.…”
Section: Evs (Exosomes) In Urinementioning
confidence: 99%
“…Thus, the more specific and ideal substrate (eg urine, prostatic plasmas and blood samples) for PCa are urgently developed rather than invasive prostate biopsies . Some studies have presented the usefulness of urinary EVs as diagnostic factors (Table ) . EV‐involved transmembrane proteins CD63 and CD9 are sufficient in urine from PCa .…”
Section: Prostate Cancermentioning
confidence: 99%
“…[136][137][138][139] Moreover, on the basis of the mass spectrometry proteome analysis, thousands of proteins encapsulated on and within vesicles are identified as biomarker candidates from urinary EVs or cell lines of PCa, [139][140][141][142][143][144][145][146] whereas the value as biomarkers is still controversial, and several types of research regenerate the previous biomarkers by the using targeted proteomics and immuno-assays. 134 Based on a proximity ligation assay, PC-derived EVs in blood has also shown to contain proteins specific to PCa, such as phosphatase 151 Donovan et al 152 Hendriks et al 153 Motamedinia et al 154 Royo et al 155 (Continues) sequencing reveals the potential values for miRNA served as diagnostic and prognostic biomarkers for PCa within serum or plasma EVs, 41,131,132,[158][159][160][161][162] such as miR-141 and miR-375 in serum, have been correlated with metastatic PCa. 159,163 Another study indicates that exosomal miR-1290 and miR-375 could be as prognostic markers in castration-resistant prostate cancer (CRPC).…”
Section: Pros Tate C An Cermentioning
confidence: 99%
“…Because of the anatomical localization of the prostate, urine appears to be an ideal substrate to detect PCa carcinogenesis. Several reports have shown the effectiveness of urinary EVs as diagnostic markers . Recently, McKiernan et al .…”
Section: Therapeutic Strategies For Urological Cancer Using Evsmentioning
confidence: 99%